Effects of pyrolysis bio-oil from palm kernel shell on bitumen properties - Nur Afeera Syakirin Abdul Manan (2022)
Sustainability and economy are the significant elements that must be considered in all fields and sectors, including the road sectors in this growing and developing nation. One alternative that can possibly achieve the sustainable and economical aspects in the road industry is by the application of sustainable pavement materials such as bitumen with renewable materials. Therefore, research on the renewable materials such as bio-oils that are obtained through pyrolysis from the local palm oil industries were conducted. Despite bio-oils improve the properties of bitumen for several researches in the existing literature reviews, the study on the effects of PKS bio-oil to bitumen properties is still limited. The objective of this study is to investigate the effects of palm kernel shell (PKS) bio-oil to the physical properties, the chemical functional group, and the morphology of the bio-oil modified bitumen. PKS bio-oil was incorporated into the bitumen by weight of bitumen at 2%, 3%, 5%, 10%, 15%, and 20% of PKS bio-oil. Bitumen modified with PKS bio-oil was compared with the control bitumen 60/70 that is commonly used as pavement in the industry. From the conventional physical test of PKS bio-oil modified bitumen, it was found that the penetration increases, softening point decreases, and the ductility increases with the addition of PKS bio-oil. For example, at 2% of PKS bio-oil modified bitumen, the penetration of the modified bitumen is found at 75dmm, in which the softening point is 46C, and the ductility is 142cm. Therefore, the physical properties test showed that the softer grade bitumen is achieved as the PKS bio-oil content increases. The functional group of bitumen which consists of carbonyl, sulfoxide, esters, aliphatic and aromatic structures are indicated through IR spectrum by the Fourier Transform Infrared Spectroscopy (FTIR) analysis and the change of the functional group is significantly influenced by the increasing content of bio-oil. From the images produced by the Scanning Electron Microscopy (SEM) analysis, the morphology of the modified bitumen with respect to the conventional control bitumen are clearly indicated that modification effect existed. Consequently, PKS bio-oil can be used as a replacement of bitumen in the region which is prone to have low temperature, hence the soften grade bitumen achieved for the bio-oil modified bitumen are able to slower down the hardening rate of the bitumen.